Health literacy in persons at risk of and patients with coronary heart disease: A systematic review. (January 2020) - Peltzer, Samia; Hellstern, Marc; Genske, Anna; Jünger, Saskia; Woopen, Christiane; Albus, Christian
Abstract: Background: Health literacy (HL) plays a crucial role in the maintenance and improvement of individual health. Empirical findings highlight the relation between a person's HL-level and clinical outcomes. However, the role of HL in persons at risk for coronary heart disease (CHD) and patients with CHD has not been researched conclusively. Objective: The aim of this study was to review systematically the current evidence on HL, its dimensions (access to, understanding, appraisal and apply of health-related information), and its important influencing factors, with regard to CHD risk. Method: We used a mixed-methods approach. Eligible articles needed to employ a validated tool for HL or mention the concept and at least one of its dimensions. After the screening process, 14 quantitative and 27 qualitative studies were included and referred to one or more dimensions of HL. Six observational studies measured HL with a validated tool. Results: Findings suggest that patients with lower HL feel less capable to perform lifestyle changes, exhibit fewer proactive coping behaviors, are more likely to deny CHD, are generally older, are less often employed, have lower educational levels and lower socioeconomic status, experience faster physical decline, and use the healthcare system less, compared to patients with higher HL. Barriers to HL include inadequate provision of information by health providers, lack of awareness of the risk factors for CHD, perceived impairment of quality of life due to lifestyle changes, and negative experiences with the healthcare system. Facilitators include a good patient-physician relationship based on good communicative competences of health providers. Conclusions: The concept of HL yields a promising potential to understand the process from obtaining information to actual health behavior change, and the results clearly indicate the need for more systematic research on HL in CHD patients and persons at risk. Highlights: Health literacy plays a crucial role in the prevention of coronary heart disease. Low health literacy correlates with poorer coping and health behavior. Unawareness of risk factors influences health-related decision-making. Health literacy benefits from good communication between patient and health-provider.